HRM IN FOREIGN-OWNED AGRICULTURAL AND FOOD PROCESSING COMPANIES IN SERBIA - Ratković, Tatjana (Economics of Agriculture, 2015)
This paper was aimed at analysing the degree to which foreign-owned agricultural and food processing companies in Serbia implement key human resource management (HRM) processes, determining whether these processes are performed in-house or outsourced, and identifying the variables which influence the decision on performing these processes within the company or outsourcing. The analysis of data collected through a survey conducted in 42 companies has confrmed the expectations that the surveyed companies mainly perform most of HRM activities The conclusion drawn from the study is that all examined HRM activities are mainly performed in-house, rather than outsourced, while the mode of performing key HRM processes mainly depends on the size of the company and the number of employees in HR department, implying that foreign-owned companies operating in agricultural and food processing sector in this transition country need to take these variables into consideration when deciding whether to perform crucial HRM activities by themselves or outsource.